ANALYSIS OF SALES STRATEGY AND ITS IMPACT ON THE FINANCIAL STATEMENTS OF MOTORCYCLE DEALERS IN LEMBANG - Mia Oktari; Tubagus Akbar (Journal of Strategic Behaviour Accounting, 2025)
This study aims to analyze the influence of sales strategy on financial performance at a Honda motorcycle dealer located in Lembang. The approach used in this study combines theoretical concepts in sales management with financial performance indicators in the field. Various sales strategies such as promotional activities, customer service, pricing, and distribution channel optimization were analyzed to see the extent of their contribution to revenue, profit margins, and overall financial health. The results of the study show that a well-designed and consistently executed sales strategy is able to have a significant positive impact on improving the dealer's financial performance, as well as supporting business growth and sustainability in competitive market competition.